Seasonal variability of aerosol concentration and size distribution in Cape Verde using a continuous aerosol optical spectrometer - Pio, Casimiro A.; Cardoso, João G.; Cerqueira, Mário A.; Calvo, Ana; Nunes, Teresa V.; Alves, Célia A.; Custódio, Danilo; Almeida, Susana M.; Almeida-Silva, Marina (Frontiers in Environmental Science, 2014)
One year of, almost continuous, measurements of aerosol optical properties and chemical composition were performed at the outskirts of Praia, Santiago Island, Cape Verde, within the framework of CV-DUST (Atmospheric aerosol in Cape Verde region: seasonal evaluation of composition, sources and transport) research project, during 2011. This article reports the aerosol number and mass concentration measurements using a GRIMM Optical Aerosol Spectrometer that provides number size discrimination into 31 size ranges from 0.25 to 32 µm. Time series of 5 min average PM10 concentrations revealed peak values higher than 1000 µg.m-3 during winter dust storm events originating over Northern Africa. The 24 hours average concentrations exceeded the World Health Organization (WHO) guidelines for PM2.5 and PM10 in 20% and 30% of the 2001 days, respectively. Annual average mass concentrations (±standard deviation) for PM1, PM2.5 and PM10 were 5±5, 19±21 and 48±64 µg.m-3, respectively. The annual PM2.5 and PM10 values were also above the limits prescribed by the WHO (10 and 20 µg.m-3, respectively). The aerosol mass size distribution revealed two main modes for particles smaller than 10 µm: a fine mode (0.7-0.8 µm), which possibly results of gas to particle conversion processes; and a coarse mode with maxima at 3-4 µm, which is associated with desert dust and sea salt sources. Within the coarse mode two sub-modes with maxima at 5-6 µm and 10-12 µm were frequently present.